High-quality sika deer omics data and integrative analysis reveal genic and cellular regulation of antler regeneration - Li, Zihe; Xu, Ziyu; Zhu, Lei; Qin, Tao; Ma, Jinrui; Feng, Zhanying; Yue, Huishan; Guan, Qing; Zhou, Botong; Han, Ge; Zhang, Guokun; Li, Chunyi; et al. (Genome Research, 2025)
The antler is the only organ that can fully regenerate annually in mammals. However, the regulatory pattern and mechanism of gene expression and cell differentiation during this process remain largely unknown. Here, we obtain comprehensive assembly and gene annotation of the sika deer (Cervus nippon) genome. We construct, together with large-scale chromatin accessibility and gene expression data, gene regulatory networks involved in antler regeneration, identifying four transcription factors, MYC, KLF4, NFE2L2, and JDP2, with high regulatory activity across the whole regeneration process. Comparative studies and luciferase reporter assay suggest the MYC expression driven by a cervid-specific regulatory element might be important for antler regenerative ability. We further develop a model called combinatorial TF Oriented Program (cTOP), which integrates single-cell data with bulk regulatory networks and find PRDM1, FOSL1, BACH1, and NFATC1 as potential pivotal factors in antler stem cell activation and osteogenic differentiation. Additionally, we uncover interactions within and between cell programs and pathways during the regeneration process. These findings provide insights into the gene and cell regulatory mechanisms of antler regeneration, particularly in stem cell activation and differentiation.